METODE KOMUNIKASI PENYULUH AGAMA HINDU BERBASIS ONLINE PADA MASA COVID-19 DI KECAMATAN DENPASAR TIMUR KOTA DENPASAR - Ni Luh Ari Sugiantari; I Nengah Lestawi; I Nyoman Ananda (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
The use of online-based media does not necessarily help Hindu extension workers in carrying out their duties and functions, because not all Hindus in East Denpasar District are literate in technology, especially the elderly. Another obstacle is the limitations of extension workers in creating online-based coaching content. In addition, extension workers cannot ensure that the counseling videos that have been distributed can be well received by the audience or the public. Therefore, this problem is important and interesting to be studied more deeply. Based on this background, 3 problem formulations were obtained, namely: 1) Why did Hindu extension workers use online-based communication methods during the Covid-19 period in East Denpasar District, Denpasar City?; 2) How is the use of online-based Hindu extension communication methods during the Covid-19 period in East Denpasar District, Denpasar City?; and 3) What are the implications of online-based Hindu extension communication methods during the Covid-19 period in East Denpasar District, Denpasar City?. The theories used in this study are attribution theory, persuasive communication theory, and mass media effect theory. This research is qualitative research with a case study approach. The location of this study is at the Ministry of Hindu Affairs Denpasar City. The types and sources of data used are primary and secondary data. The informant determination technique is purposive sampling. Data collection techniques include observation, interviews, documentation, literature study and online material search. The findings of the research are: (1) Hindu extension workers used online-based communication methods during the Covid-19 period in East Denpasar District, Denpasar City due to two factors, namely internal factors and external factors. (2) The process of using online-based Hindu extension communication methods during the Covid-19 period in East Denpasar District, Denpasar City is to master persuasive communication strategies well, by planning, organizing, which is then carried out Actuating and Controling to ensure that counseling provided online can be carried out properly. (3) The implications of online-based Hindu extension communication methods during the Covid-19 period in East Denpasar District, Denpasar City, have three dimensions, namely: Cognitive Effects (increased understanding), Affective Effects (attitudes), and Behavioral Effects (actions and intentions).